Study on magnetic field deviation due to manufacturing errors of the SIS100 superconducting dipole magnet. (December 2016) - Sugita, Kei; Fischer, Egbert; Mierau, Anna; Roux, Christian; Schnizer, Pierre
Highlights: Magnetic field analyses of the FAIR SIS100 dipole has been performed.​ Measured magnetic field was analyzed by simulations and geometrical measurements. Multiple production errors are supposed to be the cause of the magnetic field error. Sensitivity studies of the magnet manufacturing has been performed. Abstract: An international accelerator project, Facility for Antiproton and Ion Research in Europe (FAIR), is being constructed at Darmstadt, Germany. Central part of the accelerator chain is a superconducting heavy ion synchrotron SIS100, which accelerates injected particles from existing synchrotron SIS18, and provides them to experiment sites and further accelerators. Superconducting magnets in SIS100 are mainly superferric magnet with a Nuclotron cable. After R&D, the First of Series (FoS) main dipole magnet has been manufactured and tested successfully. However, magnetic field quality is unsatisfactory. We report on the investigation of the magnetic field quality by means of magnetic field measurements, geometrical measurements, and electromagnetic simulations.